Surgical rescue of adrenal metastasis by melanoma following treatment with vemurafenib (Revista Argentina de Cirugía, 2021)
We report the case of a patient presenting with a single melanoma metastasis in the adrenal gland, who underwent systemic treatment with vemurafenib (BRAF kinase inhibitor) in the first instance and then underwent surgery. Current literature recommends surgical treatment of melanoma metastases and supports the use of inhibitors in patients with a BRAF kinase mutation since they may improve disease control in a more sustained manner over time. Although for many years surgery was the only therapy for stage IV disease, with modern drug therapies, the situation has become more complex; this has created the challenge of determining the optimal combination and appropriate sequence of therapies; in this sense we consider it fundamental that cases such as the one presented here are discussed in tumor committee meetings.
Keywords: metastatic melanoma; surgical treatment; BRAF; vemurafenib; adrenal metastasis